Annual Plan 1993-94 Volume-VIII Government of Assam - Planning Commission (Planning Commission, 1993)
Considering the technical problems and high cost involved in making available Conventional energy like electricity to small isolated communities scattered over the two Hill Districts of Assam, decentralised energy systems based on renewable energy systems based on renewable energy sources is the answer to the energy problems of such areas. the sun, Wind, Bio-mass, animal washes as well flowing water offers an commence Non-conventional and renewable energy potential.
Government of Assam, Development Commissioner for Hill Areas